-3(1+2a)+3(8a-1)=12

Simple and best practice solution for -3(1+2a)+3(8a-1)=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(1+2a)+3(8a-1)=12 equation:


Simplifying
-3(1 + 2a) + 3(8a + -1) = 12
(1 * -3 + 2a * -3) + 3(8a + -1) = 12
(-3 + -6a) + 3(8a + -1) = 12

Reorder the terms:
-3 + -6a + 3(-1 + 8a) = 12
-3 + -6a + (-1 * 3 + 8a * 3) = 12
-3 + -6a + (-3 + 24a) = 12

Reorder the terms:
-3 + -3 + -6a + 24a = 12

Combine like terms: -3 + -3 = -6
-6 + -6a + 24a = 12

Combine like terms: -6a + 24a = 18a
-6 + 18a = 12

Solving
-6 + 18a = 12

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 18a = 12 + 6

Combine like terms: -6 + 6 = 0
0 + 18a = 12 + 6
18a = 12 + 6

Combine like terms: 12 + 6 = 18
18a = 18

Divide each side by '18'.
a = 1

Simplifying
a = 1

See similar equations:

| 9y^2-60y+66=0 | | 1/2x9x7 | | 13+4x=1+x | | -62=-7(1+3v)+8(4-v) | | 6(X+2)=4(X+10) | | -32=-2-3(1+3m) | | 13-9x=11x+31 | | 1/4(d-5) | | -4=2(-3-8n)+5(4+5n) | | 3(-8)+2-5(-8)=-14 | | -6x+36=3(3x-8) | | 2(x+3)+2=5x-7 | | 23w-w^2-126=0 | | 5a/6-7/12+3a=21/6 | | 3(7n+5)+6(n+6)=24 | | 8y-5=6y-18 | | -3.3e=-3.74 | | 11z+8y= | | 5x^2-10x+7=0 | | -12x-8=2x-2 | | 2x+2-3x=5 | | 5x-51=110-2x | | 3(-5p-1)+6(1+6p)=66 | | (n+15)/5 | | (n+15)/5 | | 2x^2=10x+24 | | 93+7x=51-2x | | 11x-33=9x+11 | | 12=3z+9 | | -14=4-(9x-1) | | (15x+5)=86+6x | | -22=3(2-7x)+7(-7x+6) |

Equations solver categories